Graphene reinforced electrical round aluminum rod and preparation method and application thereof
By introducing graphene into aluminum alloy and using composite stirring technology to prepare graphene-reinforced aluminum alloy materials, the problems of insufficient mechanical, electrical conductivity, thermal conductivity, corrosion resistance and fatigue resistance of electrical round aluminum rods have been solved, and significant performance improvements have been achieved.
Patent Information
- Application Number
- CN202510980200.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-16
- Publication Date
- 2025-10-17
AI Technical Summary
Existing electrical round aluminum rods have deficiencies in mechanical properties, electrical and thermal conductivity, corrosion resistance, high temperature performance and fatigue resistance, and cannot meet the needs of high-end industrial fields.
By introducing graphene mixed powder into aluminum alloy, using composite stirring technology (permanent magnetic stirring and ultrasonic stirring) to achieve uniform dispersion of graphene in the aluminum alloy, combined with solid refining agent to remove impurities, graphene-reinforced aluminum alloy material is prepared.
The static resistance and resistivity of graphene-enhanced aluminum alloy materials are better than those of pure copper rods, and the dynamic current carrying capacity exceeds that of electrical round aluminum rods and is close to that of pure copper rods. It has excellent mechanical properties, electrical conductivity, thermal conductivity, corrosion resistance and fatigue resistance.
Smart Images

Figure BDA0005502703900000081 
Figure BDA0005502703900000093 
Figure BDA0005502703900000096
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of production of electrical round aluminum rods, and particularly relates to a graphene reinforced electrical round aluminum rod and a preparation method and application thereof. BACKGROUND
[0002] The electrical round aluminum rod is a raw material for power transmission cables in the field of power transmission. In the prior art, most power transmission wires are made of ordinary aluminum rods as raw materials.
[0003] However, the current ordinary electrical round aluminum rod has the following defects: (1) insufficient mechanical properties: low strength, with a tensile strength of only 60-120 MPa, easy to deform or break; low hardness, with a Brinell hardness (HB) of about 20-40, poor wear resistance; (2) poor high-temperature performance stability: pure aluminum rods are significantly softened at a temperature of 150℃ or above, with a strength decrease of more than 50%, and are prone to creep when the wire is operated at a high temperature; high thermal expansion coefficient, poor dimensional stability when the temperature changes; (3) limited corrosion resistance: not only easy to oxidize, but also easy to form an aluminum oxide film on the surface, but local pitting occurs in a humid or salt spray environment; at the same time, electrochemical corrosion is also very serious, and when in contact with dissimilar metals such as copper and steel (such as a copper-aluminum joint), galvanic corrosion is caused by a potential difference, and a plating layer or a transition joint is needed for isolation; (4) contradiction between electrical conductivity and thermal conductivity: insufficient electrical conductivity, with an electrical conductivity of pure aluminum of 61% IACS (international annealed copper standard), which is better than steel, but only 61% of copper, and a larger cross-sectional area is needed for the same load flow; limited thermal conductivity, with a thermal conductivity of 237 W / m.K, which is not as good as copper (401 W / m.K) in terms of heat dissipation efficiency in high-power devices (such as electric vehicle battery connecting pieces); (5) fatigue performance: prone to crack under cyclic loading, and the wire joint is prone to failure in a vibrating environment.
[0004] Although a rare earth high-iron aluminum alloy rod for electrical engineering has been developed in the prior art, its electrical conductivity is insufficient, with an electrical conductivity of only 59% IACS (international annealed copper standard), which is lower than that of pure aluminum (61% IACS (international annealed copper standard)), only 59% of copper, and a larger cross-sectional area is needed for the same load flow; limited thermal conductivity, with poor heat dissipation efficiency. SUMMARY
[0005] The present application aims to provide a graphene reinforced electrical round aluminum rod and a preparation method and application thereof. The graphene reinforced aluminum alloy material prepared by the present application has excellent mechanical properties (including tensile strength, yield strength, elongation, hardness), electrical conductivity and thermal conductivity, corrosion resistance and high-temperature performance, and fatigue resistance. The static resistance, resistivity and electrical conductivity of the graphene reinforced aluminum alloy material are worse than those of a pure copper rod conductor wire and better than those of an electrical round aluminum rod conductor wire, but the dynamic active power of the graphene reinforced aluminum alloy material exceeds that of the electrical round aluminum rod wire and reaches the performance of the pure copper rod wire.
[0006] In order to achieve the above object, the present application provides the following technical scheme:
[0007] The present application provides a preparation method of graphene reinforced aluminum alloy material, comprising the following steps:
[0008] Melting aluminum ingot to obtain aluminum melt;
[0009] Spraying graphene mixed powder into the aluminum melt under the first temperature condition, the first temperature ≤780℃, the graphene mixed powder comprising graphene, solid refining agent and covalent bond modified dispersant, the mass percentage of the sprayed graphene in the aluminum melt ≤1.5%; then carrying out composite stirring under the condition of temperature rising to the second temperature to obtain initial mixed melt, the composite stirring being permanent magnet stirring accompanied by ultrasonic stirring, the second temperature being 790-800℃;
[0010] Carrying out static heat preservation of the initial mixed melt under the second temperature condition to obtain mixed melt;
[0011] Carrying out casting after solid-liquid separation of the mixed melt to obtain the graphene reinforced aluminum alloy material.
[0012] Preferably, the solid refining agent comprises nitrate and / or fluorine salt; the nitrate comprises NaNO3 and / or KNO3, and the fluorine salt comprises Na3AlF6 and / or NaF.
[0013] The covalent bond modified dispersant comprises graphene oxide.
[0014] Preferably, the mass percentage of the sprayed graphene in the aluminum melt is 0.1-1.5%.
[0015] The mass percentage of the sprayed solid refining agent in the aluminum melt is 1-2%.
[0016] The mass percentage of the sprayed covalent bond modified dispersant in the aluminum melt is 0.2-0.6%.
[0017] Preferably, the first temperature is 700-780℃.
[0018] Preferably, the spraying adopts inert gas carrier to transport the graphene mixed powder, and then the graphene mixed powder is sprayed into the aluminum melt by a spray head; the spraying condition comprises that the purity of the inert gas carrier is ≥99.99%, the pressure is 0.3-0.9MPa, and the powder spraying rate is 80-130g / min; the spray head is located at the middle part of the aluminum melt.
[0019] Preferably, the time of the complex stirring is 10-30 min; the magnetic field intensity of the permanent magnetic stirring is 0.2-0.4T, and the power density of the ultrasonic stirring is 50-200W / cm 2 , and the frequency is 20-40kHz.
[0020] Preferably, the time of the standing and heat preservation is 10-20 min.
[0021] Preferably, the graphene reinforced aluminum alloy material comprises the following mass contents of elements: C element 0.0151-0.0169%, Si element 0.044-0.136%, Fe element 0.003-0.127%, Cu element 0.001-0.002%, Mn element 0.001-0.002%, Mg element 0.002-0.003%, Cr element 0.004-0.005%, Ni element 0.003-0.005%, Pb element 0.001%, Ti element 0.001%, Zn element 0.004-0.006%, and the balance is Al element.
[0022] The application provides a graphene reinforced aluminum alloy material prepared by the preparation method.
[0023] The application provides an application of the graphene reinforced aluminum alloy material in an electrical round aluminum rod.
[0024] The application provides a preparation method of a graphene reinforced aluminum alloy material, comprising the following steps: smelting an aluminum ingot to obtain an aluminum melt; under a first temperature condition, spraying a graphene mixed powder into the aluminum melt, the first temperature being less than or equal to 780 DEG C, the graphene mixed powder comprising graphene, a solid refining agent and a covalent bond modified dispersant, the mass of the sprayed graphene accounting for less than or equal to 1.5% of the mass of the aluminum melt; then performing composite stirring under the condition of temperature rise, heating to a second temperature to obtain an initial mixed melt, the composite stirring being permanent magnet stirring accompanied by ultrasonic stirring, the second temperature being 790-800 DEG C; under the second temperature condition, the initial mixed melt is allowed to stand and keep warm to obtain a mixed melt; after solid-liquid separation of the mixed melt, casting is performed to obtain the graphene reinforced aluminum alloy material. The graphene mixed powder is used to optimize the performance of the aluminum alloy, the graphene in the graphene mixed powder can effectively improve the mechanical properties, electrical conductivity and thermal conductivity, corrosion resistance and high temperature performance and fatigue resistance of the aluminum alloy; meanwhile, the solid refining agent can further remove impurity components in the aluminum alloy, and the covalent bond modified dispersant can improve the dispersion uniformity of the graphene in the aluminum melt; meanwhile, the application optimizes the way, temperature and mixing mode of adding the graphene mixed powder into the aluminum melt, effectively solves the agglomeration problem of the graphene in the aluminum melt, realizes the uniform dispersion of the graphene in the aluminum melt, then removes impurities in the melt through standing and keeping warm, and finally obtains the graphene reinforced aluminum alloy material through casting. The graphene reinforced aluminum alloy material prepared by the application has excellent mechanical properties (including tensile strength, yield strength, elongation, hardness), electrical conductivity and thermal conductivity, corrosion resistance and high temperature performance and fatigue resistance, the static resistance, resistivity and conductivity of the graphene reinforced aluminum alloy material are worse than those of a pure copper rod conductor wire and better than those of an electrical round aluminum rod conductor wire, but the dynamic power performance of the graphene reinforced aluminum alloy material exceeds that of the electrical round aluminum rod wire and reaches the performance of the pure copper rod wire. DETAILED DESCRIPTION
[0025] The application provides a preparation method of a graphene reinforced aluminum alloy material, comprising the following steps:
[0026] Smelting an aluminum ingot to obtain an aluminum melt;
[0027] Under a first temperature condition, spraying a graphene mixed powder into the aluminum melt, the first temperature being less than or equal to 780 DEG C, the graphene mixed powder comprising graphene, a solid refining agent and a covalent bond modified dispersant, the mass of the sprayed graphene accounting for less than or equal to 1.5% of the mass of the aluminum melt; then performing composite stirring under the condition of temperature rise, heating to a second temperature to obtain an initial mixed melt, the composite stirring being permanent magnet stirring accompanied by ultrasonic stirring, the second temperature being 790-800 DEG C;
[0028] The initial mixed melt is kept at a second temperature condition to obtain a mixed melt;
[0029] The mixed melt is solid-liquid separated and then cast to obtain the graphene reinforced aluminum alloy material.
[0030] In the present application, all the raw materials / components are commercially available products well known to those skilled in the art, unless otherwise specified.
[0031] In the present application, the aluminum ingot preferably contains trace elements, which preferably include Si element, Fe element, Cu element, Mn element, Mg element, Cr element, Ni element, Pb element, Ti element and Zn element. The element composition and element mass content of the aluminum ingot are preferably determined according to the element composition of the target product graphene reinforced aluminum alloy material except for C element. The smelting preferably includes heating the aluminum ingot to melting to obtain an aluminum melt. The melting temperature is preferably 670-760℃. The melting process is preferably covered with a solvent to prevent oxidation.
[0032] After obtaining the aluminum melt, the present application sprays graphene mixed powder into the aluminum melt under a first temperature condition, the first temperature ≤780℃, the graphene mixed powder includes graphene, solid refining agent and covalent bond modified dispersant, the mass of the sprayed graphene accounts for ≤1.5% of the mass of the aluminum melt; then composite stirring is carried out under the condition of temperature rise to obtain an initial mixed melt, the composite stirring is permanent magnet stirring accompanied by ultrasonic stirring, and the second temperature is 790-800℃. In the present application, the first temperature is preferably 700-780℃. The spraying is preferably carried out in an aluminum refining furnace.
[0033] In the present application, the purity of the graphene is preferably 99-99.99%. The sheet structure size of the graphene is preferably 200-500nm. The number of layers of carbon atoms of the graphene is preferably <10 layers. The thickness of the graphene is preferably 0.35-2nm. The specific surface area of the graphene is preferably ≥300m 2 / g. The content of metal element impurities in the graphene is preferably <1000ppm. The density of the graphene is preferably <2.20g / cm 3 .
[0034] In the present application, the solid refining agent preferably includes nitrate and / or fluorine salt; the nitrate preferably includes NaNO3 and / or KNO3. The fluorine salt preferably includes Na3AlF6 and / or NaF.
[0035] In the present application, the covalent bond modified dispersant preferably comprises graphene oxide. In the present application, the graphene oxide (GO) contains carboxyl, hydroxyl, and epoxy groups. The covalent bond modified dispersant can improve the interfacial bonding compatibility of graphene with aluminum melt.
[0036] In the present application, the mass percentage of the injected graphene in the aluminum melt is preferably 0.1-1.5%, preferably 0.2-1%, and further preferably 0.3-0.8%, and in the examples, it can be 0.5% or 0.3%.
[0037] In the present application, the mass percentage of the injected solid refining agent in the aluminum melt is 1-2%, and in the examples, it can be 2%.
[0038] In the present application, the mass percentage of the injected covalent bond modified dispersant in the aluminum melt is 0.2-0.6%, and in the examples, it can be 0.6% or 0.4%.
[0039] In the present application, most of the substances in the graphene mixed powder are burned and volatilized, and the elemental composition of the graphene reinforced aluminum alloy material prepared in the present application is determined by the final determination of the elemental composition of the graphene reinforced aluminum alloy material.
[0040] In the present application, the injection is preferably performed by an electric powder injection machine, which is provided with a spray head. The motor of the electric powder injection machine is preferably used to control the powder injection rate. The injection preferably uses an inert gas carrier to transport the graphene mixed powder, which is then sprayed into the aluminum melt by the spray head. The injection conditions include that the inert gas carrier is preferably argon. The purity of the inert gas carrier is preferably ≥99.99%, and the pressure of the inert gas carrier is preferably 0.3-0.9 MPa, more preferably 0.4-0.7 MPa, and further preferably 0.5 MPa. The powder injection rate is preferably 80-130 g / min, more preferably 90-120 g / min, and further preferably 100-120 g / min. The spray head is preferably located at the middle part of the aluminum melt. The use of high-purity inert gas carrier in the present application can avoid the oxidation of graphene mixed powder and aluminum melt. The present application preferably controls the pressure of the inert gas carrier, the powder injection rate, and the position of the spray head to effectively promote the diffusion of the graphene mixed powder in the aluminum melt. In the present application, the material of the spray head is preferably a high-temperature resistant material, which preferably comprises graphite or ceramic, so as to ensure that the spray head does not melt and damage when inserted into the middle part of the aluminum melt.
[0041] In the present application, the time of the composite stirring is preferably 10-30 min, more preferably 20-30 min. The magnetic field strength of the permanent magnetic stirring is preferably 0.2-0.4 T, more preferably 0.25-0.3 T. The power density of the ultrasonic stirring is preferably 50-200 W / cm 2 , more preferably 100-150 W / cm 2 . The frequency of the ultrasonic stirring is preferably 20-40 kHz, more preferably 25-35 kHz.
[0042] In the present application, the permanent magnetic stirring accompanied by ultrasonic stirring is a composite method, i.e. the permanent magnetic stirring and the ultrasonic stirring are carried out simultaneously, which can effectively improve the dispersibility of the graphene mixed powder, improve the melt uniformity and refine the structure.
[0043] In the present application, the permanent magnetic stirring is to drive the melt convection to form vortex by the rotating magnetic field generated by the permanent magnet, and the magnetic field strength of the permanent magnetic stirring is preferably 0.2-0.4 T, which can force the graphene mixed powder to enter the inside of the aluminum melt, while avoiding the pollution caused by mechanical stirring.
[0044] In the present application, the main role of the ultrasonic stirring is auxiliary stirring, and the ultrasonic probe used in the ultrasonic stirring is preferably a titanium alloy ultrasonic probe. In the present application, the ultrasonic probe is preferably inserted into the middle part of the aluminum melt. The ultrasonic stirring preferably controls the cavitation effect of high-frequency ultrasonic waves (20-40 kHz) to break the agglomerates, and the collapse of cavitation bubbles generates local high temperature and high pressure (≈5000 K, 1000 atm), which can destroy the agglomeration of the graphene mixed powder and promote the uniform distribution of the graphene mixed powder.
[0045] After obtaining the initial mixed melt, the initial mixed melt is subjected to static heat preservation under a second temperature condition in the present application to obtain a mixed melt. In the present application, the temperature of the static heat preservation is preferably 790℃. The time of the static heat preservation is preferably 10-20 min.
[0046] In the present application, the static heat preservation is preferably used for degassing and removing impurities, wherein the degassing is to remove hydrogen in the initial mixed melt, and the aluminum melt can absorb hydrogen, which mainly comes from the decomposition of water vapor. The removal of impurities is mainly to remove oxides (aluminum oxide), residues of solvents used in smelting, etc.
[0047] After obtaining the mixed melt, the mixed melt is subjected to solid-liquid separation in the present application, and then the mixed melt is subjected to casting to obtain the graphene reinforced aluminum alloy material. In the present application, the solid-liquid separation is preferably filtration. The filtration is preferably carried out by using a foamed ceramic filter plate. The filtration is preferably online filtration. In the present application, the flow valve control flow device system is preferably used to make the mixed melt after the solid-liquid separation flow stably into the groove body to the casting machine head.
[0048] In the present application, the method for casting preferably comprises continuous casting or extrusion molding.
[0049] In the present application, the graphene reinforced aluminum alloy material is preferably a graphene reinforced aluminum alloy rod wire.
[0050] After obtaining the graphene reinforced aluminum alloy rod wire product, the present application preferably winds and packages the graphene reinforced aluminum alloy rod wire product.
[0051] The present application provides a graphene reinforced aluminum alloy material prepared by the preparation method described above.
[0052] In the present application, the graphene reinforced aluminum alloy material preferably comprises the following mass contents of elements: C element 0.0151-0.0169%, Si element 0.044-0.136%, Fe element 0.003-0.127%, Cu element 0.001-0.002%, Mn element 0.001-0.002%, Mg element 0.002-0.003%, Cr element 0.004-0.005%, Ni element 0.003-0.005%, Pb element 0.001%, Ti element 0.001%, Zn element 0.004-0.006%, and the balance being Al element.
[0053] The present application provides an application of the graphene reinforced aluminum alloy material described above in an electrical round aluminum rod.
[0054] In order to further illustrate the present application, the technical solutions provided by the present application are described in detail below in conjunction with examples, but they should not be understood as limiting the scope of protection of the present application.
[0055] Example 1
[0056] The present application provides a preparation method of a graphene reinforced aluminum alloy rod wire, comprising the following steps:
[0057] Step 1: melt aluminum ingot (containing trace elements, and the types and mass contents of trace elements except carbon element in Table 1 are used as reference) at 760℃, cover the solvent to prevent oxidation during the melting process, and obtain aluminum melt.
[0058] Step 2: place the aluminum melt in the furnace cavity of an aluminum refining furnace, and spray graphene mixed powder into the aluminum melt at a temperature of 780℃ by using an electric powder spraying machine, wherein the graphene mixed powder is preferably graphene (purity 99.99%. The size of the flaky structure is 200nm. The number of carbon atom layers is preferably <10 layers, the thickness is 0.35-2nm, the specific surface area is 300m 2 / g, the content of metal element impurities is <1000ppm, and the density is <2.20g / cm 3), solid refining agent (NaNO3) and covalent bond modified dispersant (graphene oxide), wherein the mass of the graphene mixed powder sprayed into the aluminum melt accounts for 0.5wt% of the mass of the aluminum melt, the mass of the solid refining agent sprayed accounts for 2wt% of the mass of the aluminum melt, and the mass of the covalent bond modified dispersant sprayed accounts for 0.6wt% of the mass of the aluminum melt. The nozzle (graphite material) of the electric powder sprayer is inserted into the middle of the aluminum melt, and the graphene mixed powder is sprayed into the aluminum melt by the power of the argon (purity 99.99%) carrier, the pressure of the argon carrier is 0.9MPa, and the powder spraying rate is 130g / min.
[0059] Step 3: composite stirring: the composite stirring is carried out under the condition of temperature rise, and the composite stirring is permanent magnet stirring accompanied by ultrasonic stirring, the stirring time is 30min, the magnetic field strength of the permanent magnet stirring is 0.4T, the titanium alloy ultrasonic probe (power density is 200W / cm 2 ) is inserted into the middle of the melt, and the frequency of the ultrasonic stirring is 40kHz. Stirring until the temperature in the furnace cavity rises to 800℃, stop stirring, and obtain the initial mixed melt.
[0060] Step 4: stop stirring and stand for 20min, let the dross in the initial mixed melt float up, and remove the gas and impurities, and obtain the mixed melt.
[0061] Step 5: the mixed melt is filtered online through a foamed ceramic filter plate, and flows into the groove through a flow valve control flow device system to a casting machine head.
[0062] Step 6: the graphene reinforced aluminum alloy rod wire is obtained through a continuous casting and rolling or extrusion forming system, and the specifications include
[0063] Step 7: winding and packaging.
[0064] Example 2
[0065] The application provides a preparation method of a graphene reinforced aluminum alloy rod wire, comprising the following steps:
[0066] Step 1: melt the aluminum ingot (containing trace elements, and the types and mass contents of the trace elements except carbon elements in Table 1 are used as references) at 760℃, cover the solvent to prevent oxidation during the melting process, and obtain an aluminum melt.
[0067] Step 2: place the aluminum melt in an aluminum refining furnace cavity, and spray graphene mixed powder into the aluminum melt at a temperature of 780℃ by using an electric powder sprayer, wherein the graphene mixed powder is graphene (purity 99%, flaky structure size is 500nm, the number of carbon atom layers is preferably <10 layers, the thickness is 0.35-2nm, the specific surface area is 300m 2 / g, metal element impurity content <1000 ppm, density <2.20 g / cm 3 ), solid refining agent (NaNO3), and covalent bond modified dispersant (graphene oxide), wherein the mass of the graphene mixed powder sprayed into the aluminum melt accounts for 0.3wt% of the mass of the aluminum melt, the mass of the solid refining agent sprayed into the aluminum melt accounts for 2wt% of the mass of the aluminum melt, and the mass of the covalent bond modified dispersant sprayed into the aluminum melt accounts for 0.4wt% of the mass of the aluminum melt. The spray head (graphite material) of the electric powder sprayer is inserted into the middle position of the aluminum melt, and the graphene mixed powder is sprayed into the aluminum melt by the power of the argon (purity 99.99%) carrier, the pressure of the argon carrier is 0.3MPa, and the powder spraying rate is 80g / min.
[0068] Step 3: composite stirring: composite stirring is carried out under the condition of temperature rise, and the composite stirring is permanent magnet stirring accompanied by ultrasonic stirring, the stirring time is 20min, the magnetic field strength of the permanent magnet stirring is 0.2T, and the ultrasonic stirring adopts a titanium alloy ultrasonic probe (power density is 50W / cm 2 ) inserted into the middle of the melt, and the frequency of the ultrasonic stirring is 20kHz. Stirring until the temperature in the furnace cavity rises to 800℃, stop stirring, and obtain the initial mixed melt.
[0069] Step 4: stop stirring and stand for 30min, let the dross in the initial mixed melt float up, remove the gas and impurities, and obtain the mixed melt.
[0070] Step 5: the mixed melt is filtered online through a foamed ceramic filter plate, and flows into the groove through a flow valve control flow device system to a casting machine head.
[0071] Step 6: obtain the graphene reinforced aluminum alloy rod wire through a continuous casting and rolling or extrusion molding system, and the specifications include
[0072] Step 7: winding and packaging.
[0073] The graphene mixed powder addition amount in example 1 and example 2 is 0.5wt% and 0.3wt% of the graphene addition amount of the aluminum melt, but most of the graphene mixed powder is burned and volatilized. The total ingredient formula and content mass ratio wt% of the graphene reinforced aluminum alloy rod wire prepared in example 1 and example 2 are shown in table 1 (this data is the finished product ingredient data, not the manufacturing process addition formula data, and there are metal or non-metal element burning loss factors in the manufacturing process).
[0074] Table 1 element composition of graphene reinforced aluminum alloy rod wire prepared in example 1 and example 2
[0075]
[0076] Test Example 1
[0077] The properties of the graphene reinforced aluminum alloy rod wire prepared in Example 1 were tested, and the test results are as follows:
[0078] (1) The mechanical and electrical properties of the graphene reinforced aluminum alloy rod wire prepared in Example 1 are shown in Table 2.
[0079] Table 2 Mechanical and electrical properties of the graphene reinforced aluminum alloy rod wire prepared in Example 1
[0080]
[0081] (2) The mechanical and electrical properties of the graphene reinforced aluminum alloy rod wire prepared in Example 2 are shown in Table 3.
[0082] Table 3 Mechanical and electrical properties of the graphene reinforced aluminum alloy rod wire prepared in Example 2
[0083]
[0084] Test Example 2
[0085] The graphene reinforced aluminum alloy rod wire prepared in the present application was compared with the conventional electrical round aluminum rod in terms of performance, and the conclusion is as follows:
[0086] (1) Density (g / cm3): The density of the graphene reinforced aluminum alloy rod wire is 2.7 g / cm3, which is the same as that of the electrical round aluminum rod wire.
[0087] (2) Thermal conductivity (W / m·K): The thermal conductivity of the graphene reinforced aluminum alloy rod wire is 255-300 W / m·K, which is better than that of the electrical round aluminum rod wire (237 W / m·K).
[0088] (3) Current carrying capacity: The resistance and resistivity of the graphene reinforced aluminum alloy rod wire are significantly better than those of the electrical round aluminum rod wire under static conditions, but under dynamic active conditions, the current carrying capacity of the graphene reinforced aluminum alloy rod wire is significantly higher than that of the electrical round aluminum rod wire, reaching even better than that of pure copper rod wire.
[0089] (4) Elongation: It is basically the same as that of the electrical round aluminum rod
[0090] (5) Tensile strength:
[0091] Electrical round aluminum rod (parameters): Pure aluminum rod: 60-95 MPa; other aluminum alloy rods (electrical round aluminum rod grades: 6101, 6102, 8A07, 8030, 8E76, 8R76): 95-220 MPa.
[0092] The graphene reinforced aluminum alloy rod wire prepared by the application: 110-380 MPa;
[0093] (6) Typical resistivity parameter range
[0094] Electrical round pure aluminum rod: 0.0282 Ω·mm 2 / m;
[0095] The graphene reinforced aluminum alloy rod wire prepared by the application: 0.0210-0.0274 Ω·mm2 / m; The uniform distribution of graphene in the aluminum alloy can reduce the resistivity; Interface contact resistance: graphene-aluminum interface defects will increase the resistance.
[0096] (7) Application field: graphene reinforced aluminum alloy rod wire compared with electrical round aluminum rod wire and pure copper wire: in mechanical properties, electrical properties, thermal properties, corrosion resistance and other aspects, it has obvious advantages, especially in high-end industrial fields such as: aerospace, power transmission, new energy vehicles, wind and solar power, enameled wire and other fields, it shows great potential.
[0097] Test example 3:
[0098] Performance test results of the graphene reinforced aluminum alloy rod wire prepared by the application:
[0099] (1) Mechanical properties
[0100] Mechanism: two-dimensional structure of graphene, ultra-high strength ≈130 GPa, through load transfer effect and dislocation pinning to enhance aluminum matrix; Graphene inhibits grain boundary sliding and refines grains (Hall-Petch effect).
[0101] Table 4 Comparison of mechanical properties of graphene reinforced aluminum alloy rod wire prepared by the application and electrical round aluminum rod
[0102]
[0103] (2) Electrical conductivity and thermal conductivity
[0104] Graphene has extremely high electrical conductivity ≈10 -6 S / m; The thermal conductivity benefits from the graphene phonon conduction path, and the in-plane thermal conductivity ≈5000 w / m.k.
[0105] Table 5 Comparison of electrical conductivity and thermal conductivity of graphene reinforced aluminum alloy rod wire prepared by the application and electrical round aluminum rod
[0106] Performance Index Electrical Round Aluminum Rod Series Graphene Reinforced Aluminum Alloy Rod Wire Change Electrical Conductivity (%IACS) 59~63 (Pure Aluminum Standard) 63~70 (0.1~1.5wt% Graphene) Up 1.5%~11.1% Thermal Conductivity (W / m·K) 237 255~300 Up 5.4%~26.5%
[0107] (3) Corrosion resistance and high temperature performance
[0108] The barrier effect of graphene delays the penetration of corrosive media (Cl - The graphene-aluminum interface forms a stable oxide layer composite film.
[0109] Table 6 Comparison of corrosion resistance and high temperature performance of graphene reinforced aluminum alloy rod wire prepared by the present application and electrical round aluminum rod
[0110] Performance Index Electrical Round Aluminum Rod Series Graphene Reinforced Aluminum Alloy Rod Wire Advantage Salt Spray Test (Hours) 500~1000 1500~3000 Corrosion Resistance Up 2~3 Times High Temperature Strength (200℃) Down More Than 50% Retained 70~80% Greenhouse Strength Significantly Enhanced Softening Resistance
[0111] (4) Lightweight and fatigue resistance
[0112] Density: The graphene addition amount is usually ≤1.5wt%, and the density of the composite material is almost unchanged (≈2.7g / cm3); Fatigue life: The cycle load life of the graphene reinforced aluminum alloy rod wire can be increased by 3-5 times (crack propagation is hindered).
[0113] (5) Performance of graphene reinforced aluminum alloy rod wire is compared with national standard GB / T3954-2022 (replaces GB / T3954-2014 Electrical round aluminum rod; GB / T29920-2013 Rare earth high iron aluminum alloy rod for electrical engineering); Note: O represents annealed soft wire, H12 represents 1 / 4 hard (25%), H14 represents 1 / 2 hard (50%), H15 represents 3 / 4 hard (75%), H16 represents 5 / 6 hard (≈83%), and H18 represents full hard (100%). As can be seen from the data in Table 7, the performance of the graphene reinforced aluminum alloy rod wire prepared by the present application is more excellent than that of the electrical round aluminum rod wire in Table 7.
[0114] Table 7 Performance of electrical round aluminum rod wire
[0115]
[0116]
[0117] As can be seen from the above examples, the present application uses graphene mixed powder to refine the aluminum melt, introduces graphene into the aluminum alloy, and realizes the full dispersion of graphene in the aluminum alloy by using composite stirring (permanent magnetic stirring + ultrasonic stirring), solves the pollution problem of iron impurities caused by mechanical stirring by using permanent magnetic stirring, and solves the agglomeration problem of graphene nanometer powder by using ultrasonic stirring, thereby realizing the world difficult problem of graphene and aluminum eutectic interface combination. The graphene reinforced aluminum alloy rod wire prepared by the present application overturns the existing theory and scientific new discovery that its static resistance and resistivity and conductivity are worse than pure copper rod conductor wire and better than electrical round aluminum rod conductor wire, but its electric performance load capacity exceeds that of electrical round aluminum rod wire and even reaches or is better than that of pure copper rod wire in dynamic active power condition.
[0118] Although the above embodiments have been described in detail, it should be understood that these are only some embodiments of the present application, but not all embodiments, and other embodiments can be obtained without creativity on the basis of the above embodiments, and these embodiments all belong to the protection scope of the present application.
Claims
1. A method for preparing a graphene-enhanced aluminum alloy material, characterized in that: The following steps are involved: Melting the aluminum ingot to obtain aluminum melt; Under a first temperature condition, a graphene mixed powder is sprayed into the aluminum melt, wherein the first temperature is ≤780° C., the graphene mixed powder comprises graphene, a solid refining agent, and a covalent bond modified dispersant, and the mass of the sprayed graphene accounts for ≤1.5% of the mass of the aluminum melt; then, composite stirring is performed under a heating condition, and the temperature is raised to a second temperature to obtain an initial mixed melt, wherein the composite stirring is permanent magnetic stirring accompanied by ultrasonic stirring, and the second temperature is 790-800° C.; The initial mixed melt is kept still under a second temperature condition to obtain a mixed melt; The mixed melt is subjected to solid-liquid separation and then cast to obtain the graphene-reinforced aluminum alloy material.
2. The preparation method according to claim 1, characterized in that The solid refining agent includes nitrate and / or fluoride salt; the nitrate includes NaNO3 and / or KNO3, and the fluoride salt includes Na3AlF6 and / or NaF; The covalently modified dispersant includes graphene oxide.
3. The preparation method according to claim 1 or 2, characterized in that The mass of the injected graphene accounts for 0.1 to 1.5% of the mass of the aluminum melt; The mass of the injected solid refining agent accounts for 1 to 2% of the mass of the aluminum melt; The mass percentage of the injected covalent bond modified dispersant to the mass of the aluminum melt is 0.2-0.6%.
4. The preparation method according to claim 1, characterized in that The first temperature is 700-780°C.
5. The preparation method according to claim 1 or 4, characterized in that The spraying uses an inert gas carrier to transport the graphene mixed powder, and then the graphene mixed powder is sprayed into the aluminum melt by a nozzle; the conditions for the spraying include: the purity of the inert gas carrier is ≥99.99%, the pressure is 0.3-0.9 MPa, and the powder spraying rate is 80-130 g / min; the nozzle is located in the middle of the aluminum melt.
6. The preparation method according to claim 1, characterized in that The composite stirring time is 10 to 30 minutes; the magnetic field strength of the permanent magnetic stirring is 0.2 to 0.4 T, and the power density of the ultrasonic stirring is 50 to 200 W / cm 2 , frequency is 20~40kHz.
7. The preparation method according to claim 1, characterized in that The time of standing and keeping warm is 10 to 20 minutes.
8. The preparation method according to claim 1, characterized in that The graphene-enhanced aluminum alloy material includes the following elements by mass content: 0.0151-0.0169% C element, 0.044-0.136% Si element, 0.003-0.127% Fe element, 0.001-0.002% Cu element, 0.001-0.002% Mn element, 0.002-0.003% Mg element, 0.004-0.005% Cr element, 0.003-0.005% Ni element, 0.001% Pb element, 0.001% Ti element, 0.004-0.006% Zn element, and the balance is Al element.
9. The graphene-reinforced aluminum alloy material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the graphene-enhanced aluminum alloy material according to claim 9 in electrical round aluminum rods.